Charalambos Bouras, Byzantine Athens, 10th-12th Centuries / Nickephoros I. Tsougarakis et al. A Companion to Latin Greece / Joanita Vroom, Medieval and Post-Medieval Ceramics in the Eastern Mediterranean / Joanita Vroom et al., Medieval Masterchef - Bintliff, John (Journal of Greek Archaeology, 2021)
Both the Bouras and Tsougarakis books are splendid introductions to their respective periods, Bouras on Middle Byzantine Athens, and the Tsougarakis-Lock edited volume on Frankish Greece. But the prices surely rule out owning a hard-copy of either book for almost all interested readers. At least Routledge offers a cheap online-version as a reasonable alternative access. Brill’s policy of matching online price to hard copy is quite unfathomable. Charalambos Bouras, who died in 2016 shortly before this volume on Athens appeared, was a giant in the field of Byzantine and Post-Byzantine Architecture, and this volume bears ample witness to his mastery of the monuments, and in particular of their historical context. It was first published by the Benaki Museum in 2010, but has been revised for this new Routledge edition. It is a fine accompaniment to his earlier excellent introduction to the architecture of Greece as a whole from Early Byzantine to the Early Modern era, published bilingually by the leading Athens publisher Melissa (Bouras 2006). This final work covers in immense detail the architectural record of Athens from the 6th through to the end of the 12th centuries AD, although very little indeed can be said of the first Byzantine period – the Early Byzantine, from the later 7th to the mid-9th centuries. At its core is a careful catalogue of some forty churches which can be assigned to the Middle Byzantine period (late 9th to the end of the 12th centuries).